Effects of different combinations of poultry manure and urea on growth, yield and economics of garlic (Allium sativum L.) - Sitaula, Hom Prasad; Dhakal, Roshan; Bhattarai, Chandan; Aryal, Amrit; Bhandari, Dija (Journal of Agriculture and Natural Resources, 2020)
A field experiment was carried out in garlic (Allium sativum L.) in Randomized Complete Block Design (RCBD) with four replications and five treatments in horticulture farm of Agriculture and Forestry University, Chitwan, Nepal to find out the efficacy of different combination of poultry manure and Urea as nitrogen fertilizers in its yield and yield attributes. The five treatments used for experiment were designed altering the recommended nitrogen dose through different sources i.e. (T1) 100% Urea, (T2) 7% Urea and 25% poultry manure, (T3) 50% Urea and 50% poultry manure, (T4) 25% Urea and 75% poultry manure and (T5) 100% poultry manure. The data regarding to the plant height, number of cloves, diameter of bulbs and fresh bulb weight were taken. In case of plant height, non-significant result was found between various treatments. The number of cloves was found highest in T5 (24.69±1.30), the diameter of bulb was found highest in T2 (3.93±0.39 cm), fresh bulb weight was found highest in T2 (14.32±0.39 gm) and total bulb yield was found highest in T2 (7.16±0.19 t/ha) which were significant at 5 % level of significance. The total bulb yield was found positively correlated (r=0.53) with diameter of bulb at 1 % level of significance. The benefit cost (B/C) ratio was found highest in T2 (1.54) and lowest in T3 (1.28). So 75% Urea and 25 % Poultry Manure stood one of the best combinations of nitrogen fertilizers providing higher economic yields.